PENGARUH MOTIVASI DAN KEAKTIFAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MATAKULIAH PEMBELAJARAN MATEMATIKA SD - Enny Dwi Lestariningsih; Edi Prayitno; Eko Andy Purnomo (Universitas Muhammadiyah Semarang, 2023)
This study aims to determine the effect of motivation and activeness on problem-solving abilities in learning that is applied through the implementation of android-based learning media. This type of research is experimental with a sample of UT Pokjar Kendal Regency students. The instruments used in this study were activity observation sheets, motivational questionnaires, and problem-solving ability tests. The research results show: 1). the effect of motivation on problem-solving is 76.9%, 2). the influence of activeness on problem-solving by 52.6%, and 3). the impact of motivation and activeness together on problem-solving is 84%. Based on this, it can be concluded that there is an influence of activeness and motivation on problem-solving abilities. Future research in improving problem-solving skills by increasing student activity and motivation